An equivalent equation solved for y is y = a/πx.
Two algebraic expressions having same value and symbol '=' in between are called as an equation.
Given:
The area, a, of an ellipse can be determined using the formula a = πxy, where x and y are half the lengths of the largest and smallest diameters of the ellipse.
To find an equivalent equation:
Simplifying,
a = πxy
y = a/πx
Therefore, the equation is y = a/πx
To learn more about the equation;
#SPJ6
The complete question:
The area, a, of an ellipse can be determined using the formula a = πxy, where x and y are half the lengths of the largest and smallest diameters of the ellipse. Which is an equivalent equation solved for y?
Answer:
We have the formula for determing the area of an ellipse : a = Pi * x * y, and we have to find the equivalent equation solved for y. In this formula x is half the length of the largest and y is half the length of the smallest diameter of the ellipse. Pi is approx. 3.14. Starting with: a = Pi * x * y ( we will divide both sides of the equation by: Pi * x ) => a /(Pi*x) = y. Answer: y = a / (Pi*x).
Plz mark brainliest if this helps!
The least common denominator (LCD) of the fractions 1/3 and 3/4, which is a common multiple of their denominators is: 12.
Recall:
Given two fractions, 1/3 and 3/4:
Their denominators are 3 and 4.
The common multiple between 3 and 4 is 12.
Therefore, the least common denominator (LCD) of the fractions 1/3 and 3/4, which is a common multiple of their denominators is: 12.
Learn more here:
Answer:
infinite solutions
Step-by-step explanation:
Given
- 6(n - 8) = 4(12 - 5n) + 14n ← distribute parenthesis on both sides
- 6n + 48 = 48 - 20n + 14n, that is
- 6n + 48 = 48 - 6n ( add 6n to both sides )
48 = 48 ← True
This indicates that the equation is true for any value of n
Answer:
This is a very classical type of equation in which, the solution is basically any number and it is known as an "Identity". So it has infinite solutions
Step-by-step explanation:
-6(n-8) = 4(12-5n)+14n
-6n-6*(-8) = 4*12+4*(-5n) + 14n
-6n+48=48-20n+14n
-6n+48=48-6n
-6n+48=48-6n
-6n +6n + 48 -48 = 48 -48 - 6n + 6n
0 = 0